Estudo comparativo da espacialização do MST no estado de São Paulo - 1990-2013 - Origuéla, Camila Ferracini [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The struggle for land is interpreted throughout this research as a historical-structural issue intrinsic to the formation of national territory and the development of the capitalist mode of production in the countryside, and more recently, in the city. Since the 1960s, land occupations and encampments are the main forms of struggle for access to land in the state of São Paulo and in Brazil. In the 1980s, these actions contributed to the emergence of the largest socio-territorial movement of our history: the Landless Rural Workers Movement (MST). This research aims to understand the process of the spatialization of the MST- which occurs through the organization of land occupations and encampments- in the state of São Paulo in different historical and geographical contexts. The first historical and geographical context corresponds to the late 1980s and early 1990s, in which the spatialization of the MST occurred primarily through the formation of multidimensional spaces of political socialization. The second context refers to the late 1990s and early 2000s, where there was an overlapping of the spaces of political socialization. And finally, the third context is the period from 2012 to 2014. Based on a bibliographic review, data surveys, desk research and fieldwork, mediated through semi-structured interviews and participant observation, we conclude that in recent years the land occupations and encampments of the MST have become spaces of precarious political socialization in which the socio-spatial relations and, consequently, organizational relations are sporadic.

A luta pela terra é interpretada ao longo desta pesquisa como uma questão histórico-estrutural intrínseca aos processos de formação do território nacional e de desenvolvimento do modo capitalista de produção no campo e, recentemente, na cidade. Desde a década de 1960, as ocupações de terra e os acampamentos são a principal forma de luta pelo acesso a terra no estado de São Paulo e no Brasil. Na década de 1980, essas ações contribuíram com o surgimento do principal movimento socioterritorial da nossa história: o Movimento dos Trabalhadores Rurais Sem Terra (MST). A presente pesquisa tem como objetivo compreender o processo de espacialização do MST - que ocorre por meio da organização de ocupações de terra e acampamentos - no estado de São Paulo em diferentes contextos histórico-geográficos. O primeiro contexto histórico-geográfico corresponde ao final da década de 1980 e início da década de 1990, no qual o processo de espacialização do MST ocorria por meio do multidimensionamento dos espaços de socialização política. O segundo contexto histórico-geográfico diz respeito ao final de década de 1990 e início da década de 2000, no qual houve a sobreposição dos espaços de socialização política. E, por fim, o terceiro contexto corresponde ao período de 2012 a 2013. Concluímos por meio das leituras bibliográficas, levantamentos de dados, pesquisas documentais e trabalhos de campo, mediados através de entrevistas semi-estruturadas e observação participante, que nos últimos anos as ocupações de terra e os acampamentos se transformaram em espaços de socialização política precários, nos quais as relações socioespaciais e, consequentemente, organizacionais são esporádicas.
Keywords: Geografia; Posse da terra; Camponeses; Conflitos de terra; Reforma agraria - São Paulo (Estado); Geography